ENGAGING END-USERS IN THE PROTOTYPING OF A CULTURALLY ADAPTED FAMILY-STRENGTHENING INTERVENTION FOR LATINE FAMILIES - (:unkn) unknown (My University, 2024)
Latine individuals living in mainland United States (U.S.) have been historically underrepresented in psychology intervention research, which is concerning considering the significant health and healthcare inequities facing this population as well as the fact that this segment of the overall population is rapidly increasing. Even though Human-Centered Design (HCD) holds promise for facilitating health equity efforts, it is not commonly used within the psychology field. The field requires concrete exemplars for the application of HCD principles that incorporate robust community engagement in ways that are culturally-, linguistically-, and contextually-appropriate for Latine individuals. Moreover, there is a need for the development of innovative methods that can optimally engage not just adults, but also children and adolescents in these efforts. To this end, the overarching purpose of the present mixed-methods study was to gather feedback from end-users (i.e., Latine parents, adolescents, and children) to inform the cultural adaption of a family-strengthening intervention titled “Coping Together” on aspects of agreeableness, appropriateness, understandability of the intervention, and cultural relevance. To do so, we synergized implementation science, HCD, and community-engaged approaches to involve Latine families in the adaptation process directly. Results showed that the ˆCoping Together materials shared with end-users had high levels of agreeableness, appropriateness, and cultural relevance. Results also point to mixed levels of understanding across age-groups, as well as suggestions made by participants to improve cultural relevance of materials. Reflections, lessons learned, and future directions are also described.
Keywords: Psychology; cultural adaptation; Latine; mixed-method design